Ocucaje Geology: contributions to the sedimentology and paleontology of Lomas de Ullujaya (Ica, Peru) - Alván De la Cruz, Aldo (2008)
In tertiary deposits in Pisco basin, stratigraphical sections from the localities of Lomas de Ullujaya, Ocucaje have been studied, there being distinguished outcrops that fit to lithostratigraphical units in the rate lower to middle Miocene; sedimentary and paleontological elements are being reported such as selachian teeth and pelecypods, that as a whole by means of the analysis of the stratigraphical sections interprets the sedimentary processes as records of regressive intervals inside sequences corresponding to a great marine transgression, and there it is where there are reports on species of such fossil sharks as Isurus hastalis, Isurus desori, Galeocerdo aduncus and Hemipristis serra assuming environments of transition infralitoral to circalitoral, and with regard to the geochronology, they are attributable to lower – middle Miocene beds.